The Influence of Marketing Strategy External Factors on Student Decisions With Trust As Moderator At STIE Riau Students (International Journal of Business and Information Technology, 2022)
The purpose of this study was to find out how much influence competition has on student satisfaction at STIE Mahaputra Riau, to find out how much influence prospects have on the decisions of STIE Mahaputra Riau students, to find out how much influence economic conditions have on student decisions at STIE Mahaputra Riau, to find out how much influence there is. competition on student decisions through trust in STIE Mahaputra Riau students, to find out how much influence prospects have on student decisions through trust in STIE Mahaputra Riau students, to find out how much influence economic conditions have on student decisions through trust in STIE Mahaputra Riau students. The result of this research is that competition influences the decisions of STIE Mahaputra Riau students. Prospects influence the decisions of STIE Mahaputra Riau students. Economic conditions affect the decisions of STIE Mahaputra Riau students. Trust moderates the competition on the decisions of STIE Mahaputra Riau students. Trust does not moderate the prospects for the decisions of STIE Mahaputra Riau students. Trust moderates economic conditions on the decisions of STIE Mahaputra Riau students.